2023
DOI: 10.1002/adfm.202213863
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Electronic Structure of Atomically Dispersed Nickel Sites through Boron and Nitrogen Dual Coordination Boosts Oxygen Reduction

Abstract: Atomically dispersed 3D transitional metal active sites with nitrogen coordination anchored on carbon support have emerged as a kind of promising electrocatalyst toward oxygen reduction reaction (ORR) in the field of fuel cells and metal-air cells. However, it is still a challenge to accurately modulate the coordination structure of single-atom metal sites, especially first-shell coordination, as well as identify the relationship between the geometric/electronic structure and ORR performance. Herein, a carbon-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 36 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…3i and Table S2†). 39–49 Meanwhile, the CNTs/Co–N,O-CP-based zinc–air battery exhibits only a negligible voltage drop after 130 h of continuous discharging (at 10 mA cm −2 ) (Fig. S34†), signifying superior stability.…”
Section: Resultsmentioning
confidence: 99%
“…3i and Table S2†). 39–49 Meanwhile, the CNTs/Co–N,O-CP-based zinc–air battery exhibits only a negligible voltage drop after 130 h of continuous discharging (at 10 mA cm −2 ) (Fig. S34†), signifying superior stability.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of the B atom with low electronegativity of the Zn-N 4 site can retain the 4s electrons of the central Zn atom, which endows the adjusted Zn + (3d 10 4s 1 ) structure with enough delocalized electrons to optimize the adsorption/desorption energy of the oxygen intermediates, thus enhancing the charge transfer ability during the ORR reaction. 51 Similarly, Wang et al 52 successfully prepared a novel B-doped Ni-N-C catalyst by the chemical precipitation and pyrolysis process, named as Ni-B/N-C. AC HAADF-STEM, XANES, and the corresponding FT EXAFS spectrum analysis of the Ni-B/N-C catalyst demonstrated that the single Ni atom was coordinated by three N atoms and one B atom (Ni-B 1 N 3 ). For ORR, the optimized Ni-B/N-C catalyst showed the highest E 1/2 (0.87 V vs. RHE) and J k @0.9 V (2.53 mA cm À2 ), which far exceeded that of the Ni-N-C, B/N-C, and N-C catalysts.…”
Section: B-atom-coordinated M-n X Structurementioning
confidence: 99%
“…Theoretical calculations unveiled that the structural change is due to carbon atoms in the N-doping C layer deposited into the vacant-rich site in S1 and then forming a more graphitized and stable S2 site (Figure f). In addition, modifying the local coordination environment by decorating other heteroatoms with different electronegativities (e.g., Se, S, or B) into the carbon skeleton has also shown great potential for enhancing ORR activity and stability. For example, Wang et al reported a B doping of the Ni–N–C catalyst (denoted as Ni–B/N–C), which was prepared by the chemical precipitation of the Ni-doped ZIF-8 precursor and B source and subsequent pyrolysis.…”
Section: Strategies To Mitigate Stability Issues Of Sacsmentioning
confidence: 99%